COMPRESSION PHYSIC-CHEMICAL PROPERTIES OF MILK FROM CAMEL, COW, GOAT, HUMANE AND SHEEP IN AL-MUTHANNA GOVERNMENT, IRAQ - Eabaid, Frhan ala Allah; Gatea, Eqbal A.; Hamdan, Israa Abd Alhasan (International Journal of Psychosocial Rehabilitation, 2020)
Milk is very important nutrients, that human cannot be dispensed with, in this study eight parameters of physic-chemical properties besides energy that obtained from the species that study (camel, cow, goat, sheep, and human milk) and compared between milk species. The milk samples were collected in Al- Muthanna province during the period from July- October 2018, the samples that are collected analyzed by EKO- Milk Scanner. Results that obtained from analysis input to statically analyzed by using ANOVA (version 10.spss), at significant differences at P